ANALISIS STRATEGI MANAJEMEN DENGAN MATRIKS INTERNAL-EKSTERNAL PADA HOMESCHOOLING PRIMAGAMA SOLO BARU - Yunita Primasanti (Universitas Sahid Surakarta, 2016)
The purpose of this study is to analyze management strategies in homeschooling, especially regarding opportunities and threats, especially in Primagama Solobaru Homeschooling. In this study focused on Primagama Solobaru Homescooling because the level of competition in the world of education is very high so that it influences what marketing strategies to do in order to compete competitively. The purpose of this study was to analyze the factors of strength, weakness, opportunity, threat and management strategies that must be applied to Solobaru Primagama Homeschooling. The data collection method in this study was using questionnaires and analysis using internal-external and SWOT matrices. Samples Respondents were students, management staff and instructors. The results of the analysis show that the internal environment of Primagama Solobaru Homeschooling has strength in education costs, teaching staff, promotion, market share, location and service. While the weakness factors are curriculum, school facilities, and program variations. In the external environment Primagama Solobaru Homeschooling is in a tight competition structure and growing consumer level. While the threat is to competitors who already have a strong brand. While the results of the analysis based on the internal-external matrix show that Primagama Solobaru Homeschooling must improve the education curriculum, train the teaching staff and improve infrastructure facilities to support the quality of education.